Commodity risk assessment of Momordica charantia fruits from Suriname - EFSA Panel on Plant Health (PLH); Claude Bragard; Katharina Dehnen‐Schmutz; Francesco Di Serio; Paolo Gonthier; Marie‐Agnès Jacques; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Juan A. Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal, 2021)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘High risk plants, plant products and other objects’. M. charantia fruits originating from countries where Thrips palmi is known to occur qualify as high‐risk plants. This Scientific Opinion covers the introduction risk for T. palmi posed by fruits of Momordica charantia L. imported from Suriname, taking into account the available scientific information, including the technical information provided by the National Plant Protection Organization of Suriname. The risk mitigation measures proposed in the technical dossier from Suriname were evaluated taking into account the possible limiting factors. An expert judgement is given on the likelihood of pest freedom taking into consideration the potential pest pressure in the field, the risk mitigation measures acting on the pest in the field and in the packinghouse, including uncertainties associated with the assessment. For T. palmi on M. charantia fruits from Suriname, an expert judgement is given on the likelihood of pest freedom following the evaluation of the risk mitigation measures acting on T. palmi, including any uncertainties. The Expert Knowledge Elicitation indicated, with 95% certainty that between 8,652 and 10,000 M. charantia fruits per 10,000 will be free from T. palmi.